The role of tribalism as mediator between employee empowerment and organizational commitment in Yemeni Islamic banking sector - Emam A.S.; Jais J.B.; Tabash M.I. (Sciendo, 2023)
This study examined the influence of employee empowerment on organizational commitment, and the level to which Tribalism plays a role in the relationship between the former two variables in the context of Islamic banks in Yemen. Indeed, the rationale for introducing employee empowerment is to increase levels of employees commitment to ensue positive outcomes. The interrelationships between the variables were analyzed to develop a strategy for increased organizational commitment in the Yemeni Islamic banking sector. This study used a social exchange theory to illustrate the study framework to link the relations between employee empowerment, organizational commitment, and Tribalism. This study relied on quantitative approaches. The study sample comprised of Yemeni Islamic banks employees. 450 questionnaires were distributed to employees, out of which, 292 were retrieved and deemed usable for analysis, constituting a 65% rate of response. The partial least squares structural equation modelling (PLS-SEM) was employed to analyze data and test the proposed hypotheses. The results indicated that there is a significant relationship between empowerment of the employees and their organizational commitment in Islamic banks in Yemen. More importantly, this study revealed that Tribalism is a significant mediator on the relationship between employee empowerment, and organizational commitment. 2019, Sciendo. All rights reserved.